Motivation and experiences of studying creative arts therapy among Chinese doctoral students in South Korea - Mo, Ya Nan; Ko, Kyung Soon (Journal of International Students, 2024)
Chinese students accounted for 40.4% of international students in South Korea in 2022. Universities in China require doctoral degrees to teach art. Creative arts therapy has increasingly gained attention. This study investigated the experiences of six Chinese students in a study abroad program for creative arts therapy in South Korea. We gathered data from visual artworks and interviews. The analysis yielded six themes: No doctoral degree, no job position for art educators in university, China; Expectations for the development of CAT in China; Despite majoring in art, CAT is a new discipline; Study abroad while unprepared in terms of language ability; Wanting to escape due to academic pressure; Motivation to continue studying abroad. Findings revealed that psychological and emotional support programs would help international students across different nationalities and cultures. Students’ study abroad experience and how it contributes to their lives beyond obtaining a degree requires further consideration.